The Relationship Between Glycemic Control And Lipid Profile In Patients With Type 2 Diabetes Mellitus In Bangli Hospital - Agustia Pradnyani, Made Ayu; Sutarjana, I Ketut (Jurnal Health Sains, 2024)
Type 2 diabetes mellitus (DM) is prone to diabetic dyslipidemia which is one of the factors in increasing the risk of cardiovascular disease complications. The purpose of this study was to determine the relationship between glycemic control and lipid profile in patients with type 2 DM. Research with a cross-sectional study was conducted at the Internal Medicine Polyclinic of Bangli Hospital in the period January 2023-December 2023 and as many as 60 patients with type 2 DM who met the inclusion criteria. Patients were grouped into type 2 DM patients with controlled glycemic control (HbA1c <7%) and uncontrolled (HbA1c ≥7%). Lower levels of total cholesterol (160,444 ± 30,608 mg/dl vs 203,476 ± 45,471 mg/dl; p = 0.001), triglycerides (125,500 ± 56,019 vs 202,047 ± 91,568; p = 0.002), low-density lipoprotein (K-LDL) (93,072 ± 28,443 vs 131,571 ± 44,590; p = 0.001) in type 2 DM patients with controlled glycemic control. High-density lipoprotein (K-HDL) levels (50,022 ± 14,050 vs 41,152 ± 12,619; p = 0.019) were higher in type 2 DM patients with controlled glycemic control. Statistical tests showed a positive correlation between total cholesterol (r = 0.277; p = 0.032), triglyceride (r = 0.386; p = 0.002) and K-LDL (r = 0.357; p = 0.005) levels with HbA1c levels. There was a negative correlation between K-HDL (r=-0.366; p=0.004) and HbA1c levels. The significant correlation between HbA1c and lipid profile shows the importance of glycemic control in type 2 DM patients. This can be explained in the pathogenesis of type 2 DM during the advanced phase. There was a positive correlation between glycemic control (HbA1c) with total cholesterol, triglycerides and K-LDL. There is a negative correlation between glycemic control (HbA1c) and K-HDL.